Identification and characterization of Colletotrichum spp. affecting fruit after harvest in Brazil - Peres, NAR; Kuramae, E. E.; Dias, MSC; de Souza, N. L. (Blackwell Verlag Gmbh, 2002)
Colletotrichum spp. cause anthracnose in various fruits post-harvest and are a particularly important problem in tropical and subtropical fruits. The disease in fruits of avocado, guava, papaya, mango and passion fruit has been reported to be caused by C. gloeosporioides, and in banana by C. musae. In subtropical and temperate crops such apple, grape, peach and kiwi, the disease is caused by C. acutatum. The variation in pathogenic, morphological, cultural and molecular characteristics of Brazilian isolates of Colletotrichum acutatum Simmonds and isolates from post-harvest decays of avocado, banana, guava, papaya, mango and passion fruit was evaluated. The fruits were inoculated with mycelium of C. acutatum, Colletotrichum spp. and C. musae on a disc of potato dextrose agar. The morphological, cultural and molecular characteristics studied were conidia morphology, colony growth at different temperatures, colony coloration and PCR with primers CaInt2 and ITS4 for C. acutatum and CgInt and ITS4 for C. gloeosporioides. C. acutatum was pathogenic to avocado, guava, papaya, mango and passion fruit, but it was not pathogenic to banana. The morphological, cultural and molecular studies indicated that the avocado, papaya, mango and passion fruit isolates were C. gloeosporioides. The natural guava isolate was identified as C. acutatum, which had not been found previously to produce anthracnose symptoms on guava in Brazil.
Keywords: Anthracnose; guava; avocado; papaya; mango; passion fruit; banana